The evaluation of the prevalence of disease among the cats and dogs admitted to clinics of veterinary faculty, mustafa kemal university (2003-2006) - Nuri MAMAK; Ramazan DURGUT; Özkan GÖRGÜLÜ (Eurasian Journal of Veterinary Sciences)
The aim of this study was to evaluate the prevalence of the disease among the dogs and cats admitted to the clinic of Mustafa Kemal University Faculty of Veterinary Medicine between 1st January 2003 and 31st December 2006. Clinical examination of the 76 cats and 366 dogs were performed These animals were evaluated in breed, sex, seasons, clinical departments, and the diseases. It was observed that the disease in cats and dogs occurred due to seasonal effects (p<0.0l). and the diseases in dogs and cats commonly observed in spring and summer seasons. When the distributions of the patients admitted to Departments in Veterinary Faculty Clinics was evaluated, the patients were commonly brought to Department of Internal Medicine (n=202,46%). these were followed by Department of Surgery (n=192, 43%) and Department of Gynecology and Reproduction (n=48, 11%). Diseases were most commonly detected between 0-12 months aged in cats and dogs. Although the dogs admitted to Veterinary Faculty Clinics were male (n=224, %61). female cats (n=49, 64%) mostly brought to all the departments. Digestive system diseases were most commonly observed in cats and dogs, and these were followed by respiratory and orthopedic disturbances such as trauma, fracture and lameness. In conclusion, it was thought that the evaluation of the diseases observed In cats and dogs In this study will help to make the owners conscious of cats and dogs diseases in this region.